2022
DOI: 10.3390/atmos13050838
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Quantification of WRF Model for Rainfall Prediction over the Sichuan Basin, China

Abstract: The mesoscale Weather Research and Forecasting (WRF) model has been widely employed to forecast day-ahead rainfalls. However, the deterministic predictions from the WRF model incorporate relatively large errors due to numerical discretization, inaccuracies in initial/boundary conditions and parameterizations, etc. Among them, the uncertainties in parameterization schemes have a huge impact on the forecasting skill of rainfalls, especially over the Sichuan Basin which is located east of the Tibetan Plateau in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
3
1
Order By: Relevance
“…In addition, the average deviation and root mean square error values are relatively small. By comparing the correlation coefficients presented in this paper with those published in the literature for temperature [39], wind speed [40], and rainfall [41] in similar terrain, it can be observed in Table 6 that the calculated correlation coefficients for temperature and wind speed in this study are slightly higher than those reported in previous studies. The correlation coefficients for rainfall closely align with the published values.…”
Section: Verify Performance For Wrf Modelcontrasting
confidence: 42%
“…In addition, the average deviation and root mean square error values are relatively small. By comparing the correlation coefficients presented in this paper with those published in the literature for temperature [39], wind speed [40], and rainfall [41] in similar terrain, it can be observed in Table 6 that the calculated correlation coefficients for temperature and wind speed in this study are slightly higher than those reported in previous studies. The correlation coefficients for rainfall closely align with the published values.…”
Section: Verify Performance For Wrf Modelcontrasting
confidence: 42%
“…This study reveals the microphysical process of convective cloud and the transformation law of hydrometeors over the Plateau, which is of great significance for further understanding of the microphysical mechanism of precipitation formation and water-cycle characteristics over the Plateau, improving the parameterization of modeled cloud physical processes, and improving the level of numerical prediction. However, due to data discretization, initial and boundary conditions, and parameterization uncertainty [44], the deterministic prediction of the WRF model has a large error. Among them, the uncertainty of the parameterization scheme has a great impact on precipitation forecast technology because the microphysics scheme, convection scheme, radiation scheme, and PBL scheme in the parameterization schemes have a great impact on the accuracy of simulation of temperature, humidity, and wind field [45].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Sichuan Basin (SCB) is located in southwestern China, and is surrounded by the Tibetan Plateau (TP), the Yunnan‐Guizhou Plateau (YGP), Southeast Hills, and Daba Mountains (Bin & Xiang, 2016; Du et al., 2022; J. Li et al., 2021). Affected by terrain, the precipitation (including extreme precipitation with different duration) over the SCB exhibits a significant diurnal feature (M. G. Wu & Luo, 2019; Zheng et al., 2019), which usually begins at night, peaks between midnight and early morning, and gradually ceases after sunrise (S. Chen et al., 2019; J. Liu et al., 2021; Y. Wu et al., 2018; Zhao et al., 2020; L. Zhu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%